The complete idiot's guide to learning Latin - Harwood, Natalie (Complete idiot's guide, 2006)
Presents introductory lessons and exercises on Latin, covering first- through fifth-declension nouns, verbs, verbals, adjectives and accusatives, pronouns, adverbs, past and future tenses, and speaking and reading, and also discusses the language's history and its use in specialties such as law and medicine.